Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1042/cs19990300
|View full text |Cite
|
Sign up to set email alerts
|

Organization and reorganization of human swallowing motor cortex: implications for recovery after stroke*

Abstract: Swallowing problems can affect as many as one in three patients in the period immediately after a stroke. In some cases this can lead to serious morbidity, in particular malnutrition and pulmonary aspiration. Despite this, swallowing usually recovers to a safe level in the majority of patients within weeks. This propensity for recovery is likely to relate to how the swallowing motor cortex is organized and then reorganized after cerebral injury. In this review, we examine present knowledge on the cortical cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(59 citation statements)
references
References 30 publications
1
57
0
1
Order By: Relevance
“…It was described that lesions located in the right hemisphere cause more pharyngeal changes and that lesions in the left hemisphere cause more changes in the oral phase of swallowing (16) . Other studies on patients with stroke did not observe a relation between the presence of dysphagia and right or left hemispheric location (13,29,36,46) . A study conducted on healthy volunteers revealed that the representation of swallowing occurs bilaterally in the motor cortex, although in an asymmetrical manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was described that lesions located in the right hemisphere cause more pharyngeal changes and that lesions in the left hemisphere cause more changes in the oral phase of swallowing (16) . Other studies on patients with stroke did not observe a relation between the presence of dysphagia and right or left hemispheric location (13,29,36,46) . A study conducted on healthy volunteers revealed that the representation of swallowing occurs bilaterally in the motor cortex, although in an asymmetrical manner.…”
Section: Discussionmentioning
confidence: 99%
“…Recovery of swallowing in dysphagic patients after a CVA is associated with increased pharyngeal representation in the unaffected hemisphere, suggesting the possibility of reorganization of this hemisphere (12) . This may explain why some patients develop dysphagia and others do not despite the same location of the lesion (13) . In addition, the size of the lesion is considered to be more important than its location for the development of oropharyngeal dysphagia (29) .…”
Section: Discussionmentioning
confidence: 99%
“…[11,12] and in many other neurological diseases, such as Parkinson's disease [13] , multi system atrophy [14] , multiple sclerosis [15] , and Altzheimer disease [3] . Dysphagia [16] and bowel dysfunction are the most frequent gastrointestinal complaints reported after stroke. Previous studies have attempted to evaluate the prevalence and pathogenesis of chronic constipation after stroke [3,17] .…”
Section: Characteristics Of Neurological Lesions and Gi Symptomsmentioning
confidence: 99%
“…Patients, who become dysphagic immediately after CVA, might recover with time when the controlateral noninjured center acquires the control of the complex act of swallowing [16] . In the present study, patients were investigated after stabilization of neurological lesions following a program of motor rehabilitation.…”
Section: Characteristics Of Neurological Lesions and Gi Symptomsmentioning
confidence: 99%
“…The organizing system located in the medulla oblongata, corresponding to the interneuronal network that programs the motor pattern Recent neuroimaging studies using various techniques, such as PET, f-MRI, and MEG, have revealed that swallowing activates multiple cerebral regions including the face area of the primary sensorimotor cortex, premotor cortex, insular cortex, frontal operculum, anterior cingulate cortex, and other cerebral regions (Dziewas et al, 2003;Hamdy et al, 1999;Hamdy et al, 2000;Kern et al, 2001;Watanabe et al, 2004;Toogood et al, 2005). In particular, f-MRI research revealed that multiple cerebral regions are recruited during swallowing, most notably the anterior cingulate cortex, pericentral cortex, insula, and premotor cortex, with different degrees of symmetry between hemispheres.…”
Section: Swallowingmentioning
confidence: 99%